COMPREHENSIVE APPROACH TO SEVERITY ASSESSMENT OF CARDIOVASCULAR HEMODYNAMIC DISORDERS IN PATIENTS WITH RHABDOMYOMAS - Gregory V. Revunenkov; Tatyana N. Petrenets (Педиатрическая фармакология)
Space-occupying lesions in the heart refer to a rare congenital pathology with incidence of 0.32% in pediatric practice. In recent years, the detection  frequency  of this pathology  has increased  due to the achievements  of early diagnostics  (including prenatal diagnostics),  integration of high volume scanning and high-quality ultrasound images. The greatest number of tumors (72–77%) is detected in infants under 1 year of age, up to 26% of which — prenatally. Available international clinical data confirms the congenital nature of most heart tumors, approximately 50% are rhabdomyomas.  The presented clinical case demonstrates  the demand for a complex approach and the application of new 3D and 4D cardiac scanning in pediatric practice to assess the severity of cardiovascular damage and the prognosis of treatment in patients with rhabdomyomas of the heart.